2020
DOI: 10.3389/fnut.2020.00094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Autophagy and Apoptosis in Aged Brain: Human and Animal Studies

Abstract: The aging process is characterized by a series of molecular and cellular changes over the years that could culminate in the deterioration of physiological parameters important to keeping an organism alive and healthy. Physical exercise, defined as planned, structured and repetitive physical activity, has been an important force to alter physiology and brain development during the process of human beings' evolution. Among several aspects of aging, the aim of this review is to discuss the balance between two vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 235 publications
(276 reference statements)
1
19
0
1
Order By: Relevance
“…Not only pharmacological treatment may cause upregulation of autophagy. Also physical exercises and diet were found to have a positive effect on both autophagy and the brain function (Andreotti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only pharmacological treatment may cause upregulation of autophagy. Also physical exercises and diet were found to have a positive effect on both autophagy and the brain function (Andreotti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is a well-established lifestyle modification that retards aging and increases human healthspan [ 283 ]. Exercise enhances mitophagy and autophagy [ 284 , 285 ], which are associated with the inhibition of mPTP. It was shown that exercise training decreases susceptibility to Ca 2+ -induced mPTP opening in heart mitochondria [ 286 ].…”
Section: Lifespan and Healthspan Extension Paradigms And Mptpmentioning
confidence: 99%
“…ECT rapidly and transiently induces autophagy in the hippocampus [ 119 ], consistent with the rapid and transient antidepressant effect in patients. The antidepressant effects of physical activity [ 120 , 121 ] are compatible with increased autophagy [ 122 , 123 , 124 ]. Mediterranean and other healthy diets have preventive and therapeutic effects on future [ 125 , 126 ] and current [ 127 ] depressive episodes.…”
Section: Sphingolipids In Mddmentioning
confidence: 99%